2016
DOI: 10.1186/s12889-016-3493-z
|View full text |Cite
|
Sign up to set email alerts
|

An individually-tailored smoking cessation intervention for rural Veterans: a pilot randomized trial

Abstract: BackgroundTobacco use remains prevalent among Veterans of military service and those residing in rural areas. Smokers frequently experience tobacco-related issues including risky alcohol use, post-cessation weight gain, and depressive symptoms that may adversely impact their likelihood of quitting and maintaining abstinence. Telephone-based interventions that simultaneously address these issues may help to increase treatment access and improve outcomes.MethodsThis study was a two-group randomized controlled pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…40 Studies have also evaluated the feasibility of concomitantly addressing risky alcohol use and mood management in the context of smoking cessation, including in HNC patients, and have shown promise. 9,41 In this study, tobacco use and depressive symptomatology both were significantly associated with problem alcohol use, suggesting that several patients in this study may have been candidates for such multimodal intervention but requires additional research. Moreover, although only a small number of rural and urban patients reported moderate to severe depressive symptomatology, a considerable number reported mild symptoms, which are not trivial and have been associated with deficits in HNC-specific HRQOL 33 and may also be associated with drinking behavior.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…40 Studies have also evaluated the feasibility of concomitantly addressing risky alcohol use and mood management in the context of smoking cessation, including in HNC patients, and have shown promise. 9,41 In this study, tobacco use and depressive symptomatology both were significantly associated with problem alcohol use, suggesting that several patients in this study may have been candidates for such multimodal intervention but requires additional research. Moreover, although only a small number of rural and urban patients reported moderate to severe depressive symptomatology, a considerable number reported mild symptoms, which are not trivial and have been associated with deficits in HNC-specific HRQOL 33 and may also be associated with drinking behavior.…”
Section: Resultsmentioning
confidence: 77%
“…One study which interviewed rural and urban VA primary care providers on the topic of AUD treatment found that rural providers reported substantial barriers to specialty care referrals for AUD 40 . Studies have also evaluated the feasibility of concomitantly addressing risky alcohol use and mood management in the context of smoking cessation, including in HNC patients, and have shown promise 9,41 . In this study, tobacco use and depressive symptomatology both were significantly associated with problem alcohol use, suggesting that several patients in this study may have been candidates for such multimodal intervention but requires additional research.…”
Section: Discussionmentioning
confidence: 84%
“…Ishani et al (2016) evaluated provision of services by an interdisciplinary team that included social workers, comparing telehealth to treatment as usual. Social workers were involved in a trial of Accelerated Resolution Therapy for treatment of PTSD (Kip et al, 2013), smoking cessation for veterans with PTSD (McFall et al, 2005), smoking cessation for rural veterans (Vander Weg et al, 2016), and means of reducing risky drinking in older adults (Wooten et al, 2017) both as authors and providers of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Multimodal interventions for complex behavioral health cases, such as those with concomitant alcohol and smoking issues, may therefore be relevant dependent on the individual patient's needs. Interventions addressing multiple concerns at once have been tested with some success, including those dealing with smoking and drinking and in patients with HNC [21,42]. For example, Duffy and colleagues developed a tailored, multimodal intervention in which patients with HNC were treated for smoking, problem alcohol use, or probable depression, whether alone or in combination as indicated [21].…”
Section: Discussionmentioning
confidence: 99%